Comorbidity and nutritional status in adult with advanced chronic kidney disease influence the decision-making choice of renal replacement therapy modality: A retrospective 5-year study - Álvarez-García, Graciela; Nogueira Pérez, Ángel; Prieto Alaguero, María Pilar; Pérez Garrote, Carmen; Díaz Testillano, Aránzazu; Moral Caballero, Miguel Ángel; Ruperto, Mar; González Blázquez, Cristina; Barril, Guillermina (Frontiers in Nutrition, 2023)
Background Nutritional and inflammation status are significant predictors of morbidity and mortality risk in advanced chronic kidney disease (ACKD). To date, there are a limited number of clinical studies on the influence of nutritional status in ACKD stages 4–5 on the choice of renal replacement therapy (RRT) modality. Aim This study aimed to examine relationships between comorbidity and nutritional and inflammatory status and the decision-making on the choice of RRT modalities in adults with ACKD. Methods A retrospective cross-sectional study was conducted on 211 patients with ACKD with stages 4–5 from 2016 to 2021. Comorbidity was assessed using the Charlson comorbidity index (CCI) according to severity (CCI: ≤ 3 and >3 points). Clinical and nutritional assessment was carried out by prognosis nutritional index (PNI), laboratory parameters [serum s-albumin, s-prealbumin, and C-reactive protein (s-CRP)], and anthropometric measurements. The initial decision-making of the different RRT modalities [(in-center, home-based hemodialysis (HD), and peritoneal dialysis (PD)] as well as the informed therapeutic options (conservative treatment of CKD or pre-dialysis living donor transplantation) were recorded. The sample was classified according to gender, time on follow-up in the ACKD unit (≤ 6 and >6 months), and the initial decision-making of RRT (in-center and home-RRT). Univariate and multivariate regression analyses were carried out for evaluating the independent predictors of home-based RRT. Results Of the 211 patients with ACKD, 47.4% (n = 100) were in stage 5 CKD, mainly elderly men (65.4%). DM was the main etiology of CKD (22.7%) together with hypertension (96.6%) as a CV risk factor. Higher CCI scores were significantly found in men, and severe comorbidity with a CCI score > 3 points was 99.1%. The mean time of follow-up time in the ACKD unit was 9.6 ± 12.8 months. A significantly higher CCI was found in those patients with a follow-up time > 6 months, as well as higher mean values of eGFR, s-albumin, s-prealbumin, s-transferrin, and hemoglobin, and lower s-CRP than those with a follow-up <6 months (all, at least p < 0.05). The mean PNI score was 38.9 ± 5.5 points, and a PNI score ≤ 39 points was found in 36.5%. S-albumin level > 3.8 g/dl was found in 71.1% (n = 150), and values of s-CRP ≤ 1 mg/dl were 82.9% (n = 175). PEW prevalence was 15.2%. The initial choice of RRT modality was higher in in-center HD (n = 119 patients; 56.4%) than in home-based RRT (n = 81; 40.5%). Patients who chose home-based RRT had significantly lower CCI scores and higher mean values of s-albumin, s-prealbumin, s-transferrin, hemoglobin, and eGFR and lower s-CRP than those who chose in-center RRT (p < 0.001). Logistic regression demonstrated that s-albumin (OR: 0.147) and a follow-up time in the ACKD unit >6 months (OR: 0.440) were significantly associated with the likelihood of decision-making to choose a home-based RRT modality (all, at least p < 0.05). Conclusion Regular monitoring and follow-up of sociodemographic factors, comorbidity, and nutritional and inflammatory status in a multidisciplinary ACKD unit significantly influenced decision-making on the choice of RRT modality and outcome in patients with non-dialysis ACKD.